Ras Shamra Parallels. The Texts from Ugarit and the Hebrew Bible, Vol. III (1981)
Published under the auspices of the Institute for Antiquity and Christianity, Claremont, California; 1-206: M. J. Dahood, Ugaritic-Hebrew Parallel Pairs; 207] 219: R. E. Whitaker, Ugaritic Formulae; 221-332: S. Rummel, Narrative Structures in the Ugaritic Texts; 339-469: A. Cooper, Divine Names and Epithets in the Ugaritic Texts, with introduction and comments by M. H. Pope; 471-500: F. B. Knutson, Divine Names and Epithets in the Akkadian texts.